2012
DOI: 10.1002/smll.201102304
|View full text |Cite
|
Sign up to set email alerts
|

Optical Nanomanipulations of Malignant Cells: Controlled Cell Damage and Fusion

Abstract: Specifically targeting and manipulating living cells is a key challenge in biomedicine and in cancer research in particular. Several studies have shown that nanoparticles irradiated by intense lasers are capable of conveying damage to nearby cells for various therapeutic and biological applications. In this work ultrashort laser pulses and gold nanospheres are used for the generation of localized, nanometric disruptions on the membranes of specifically targeted cells. The high structural stability of the nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 51 publications
3
38
0
Order By: Relevance
“…The data shown represent percentage increase compared to control and represents the mean ± standard deviation. Taken together, these data demonstrate that AuNPs induced ROS accumulation is dose and time-dependent in lymphoma cell lines [43]. The earliest intracellular events were occurred in apoptosis due to disruption of the mitochondrial membrane potential.…”
Section: Aunps Induces Ros Accumulation In Sudhl-4 Cell Linesupporting
confidence: 58%
See 2 more Smart Citations
“…The data shown represent percentage increase compared to control and represents the mean ± standard deviation. Taken together, these data demonstrate that AuNPs induced ROS accumulation is dose and time-dependent in lymphoma cell lines [43]. The earliest intracellular events were occurred in apoptosis due to disruption of the mitochondrial membrane potential.…”
Section: Aunps Induces Ros Accumulation In Sudhl-4 Cell Linesupporting
confidence: 58%
“…That ROS played an important role in apoptosis of lymphoma cell lines SUDHL-4 was demonstrated by near complete abrogation of apoptosis by the antioxidant NAC and by enhancement of apoptosis by the GSH depleting agent BSO. These observations were not restricted to cell lines [43].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…35,36 To date, NPs-based strategies imply using of organic sensitizers (with some notable exceptions. 37 ) and are mediated by ROS generation. 18,34,38,39 As for classical phototherapy, these approaches can generate major side effects due to the presence of toxic compounds and ROS which can diffuse to nearby tissues generating oxidative stress.…”
mentioning
confidence: 99%
“…Pulses in the femtosecond range, which in some conditions may induce multiphoton ionization in addition to rapid heating [44], were reported effective in damaging cancerous HeLa cells conjugated to gold nanorods [59]. Recently, our group has shown that single resonant femtosecond laser pulses in the visible wavelength range may induce well-controlled necrosis, apoptosis and fusion of epidermoid carcinoma cells and Burkitt lymphoma cells targeted by antibody-coated gold nanospheres [60].…”
Section: Introductionmentioning
confidence: 98%